Leksikalsk materiale fra sekundære kilder og ophavsret - Lenstrup, Rita (Nordiske Studier i Leksikografi, 2003)
This subject is important in the light of the growing number of machine-readable dictionaries because they are secondary sources that are easy to copy from for inclusion in new dictionaries (Svensén 1993:62). This paper will take its starting point in the question of how much lexical material can be drawn from secondary sources such as other dictionaries for the inclusion in a new dictionary without risking to infringe upon the copyrights of others; but in particular it will focus on how we can represent what and how much we want to draw, or how much we think might have been drawn from another secondary source for the use in a new dictionary? Two Danish English LSP dictionaries have been used for the illustration of practical attempts at such comparison.